Revitalization Supervision Islamic Banking in Enhancement Compliance in Indonesia and Malaysia - Yusmad, Muammar Arafat; Irwansyah, Irwansyah; Marinsah, Syamsul Azizul Bin; Ayyub, Mukhtaram; Muang, Muh. Shadri Kahar (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This study is indicated with social reality that, following three decades of dual banking system implementation in Indonesia, Islamic banks' operational activities are essentially identical with the operations of conventional banks. The thing that distinguishes is only the Shariah "brand". In the vast zone of national banking industry, Islamic banks are still being the "followers" of conventional banks with approximately 6.65% market share. The focus of study is on the Islamic bank supervision system by DPS, the Shariah Bank Compliance Directorate, and OJK in carrying out supervisory functions related to fields of duty. The study methodology applied is a normative legal study which includes a study of norms, principles of sharia banking law, and the opinions of sharia economic law experts, while those used are a statutory approach and a sociological approach. The next stage of data analysis is data display, which illustrated through tables, figures, and graphs. Data categorization was carried out relied to the theme to identify the implementation of Islamic bank supervision duties in conforming to Shariah principles and the implementation of laws and regulations. The results showed that there are several problems in Islamic bank supervision institutions that make supervisory performance not optimal and pose potential legal risks for the bank. The roles of DPS, the Directorate of Shariah Bank Compliance, and OJK, which run independently and inefficiently, create overlapping aspects of Islamic bank supervision. This study recommends amending UURI No. 21 of 2008 about Shariah Banking by giving attributive responsibility to DPS to sanction Islamic banks that proved to violate Shariah principal compliance and establishing the OJK regulations on Islamic banking audit instruments.